2022
DOI: 10.1111/jcpe.13751
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet component oleic acid increases protective lipid mediators and improves trabecular bone in a Porphyromonas gingivalis inoculation model

Abstract: Aim Therapeutic modulation of bacterial‐induced inflammatory host response is being investigated in gingival inflammation and periodontal disease pathology. Therefore, dietary intake of the monounsaturated fatty acid (FA) oleic acid (OA (C18:1)), which is the main component of Mediterranean‐style diets, and saturated FA palmitic acid (PA (C16:0)), which is a component of Western‐style diets, was investigated for their modifying potential in an oral inoculation model of Porphyromonas gingivalis. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Recent findings have described OA-ED as pro-resolving by enhancing serological RvD4 and 4-HDHA levels. Besides being pro-resolving, these lipid mediators reduced Tnfα -expression in gingival fibroblasts (GFb), which, downstream, could impact the microenvironment and reduce osteoclastic differentiation in GFb-co-cultures ( 27 ). Decreased osteoclast numbers in P. gingivalis -infected animals on OA-ED suggested that OA-intake actively impacts cells and their surrounding by advancing resolution, thereby improving bone microarchitecture in the oral cavity ( 27 ) and modifying cellular response to oral P. gingivalis inoculation in systemic bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent findings have described OA-ED as pro-resolving by enhancing serological RvD4 and 4-HDHA levels. Besides being pro-resolving, these lipid mediators reduced Tnfα -expression in gingival fibroblasts (GFb), which, downstream, could impact the microenvironment and reduce osteoclastic differentiation in GFb-co-cultures ( 27 ). Decreased osteoclast numbers in P. gingivalis -infected animals on OA-ED suggested that OA-intake actively impacts cells and their surrounding by advancing resolution, thereby improving bone microarchitecture in the oral cavity ( 27 ) and modifying cellular response to oral P. gingivalis inoculation in systemic bone.…”
Section: Discussionmentioning
confidence: 99%
“…After one initial week of acclimatization, 4-week-old male C57BL/6 wildtype mice were randomly divided into groups (n=12/group) and put on either PA or OA-enriched diets (PA-ED, OA-ED) (21% calories from fat) (Ssniff, Soest, Germany) or a standard diet (ND) (11% calories from fat) for a total of 16 weeks as described before ( Table S1 ) ( 27 ). Animals were assigned blinded number codes, which were used throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by a generous consumption of whole grains, fruits, vegetables, legumes, and olive oil while emphasizing moderation in dairy products and alcohol, and limiting meat intake ( 112 ). Animal studies have demonstrated that the primary component of the Mediterranean diet, oleic acid, exhibits remarkable anti-inflammatory properties, and also contributes to the resolution of inflammation, thereby ameliorating tissue damage resulting from the host response to oral bacterial ingestion in mice ( 113 ). Mild cognitive impairment (MCI) represents an early stage of AD pathology and necessitates non-pharmacological interventions, including dietary and nutritional modifications.…”
Section: The Potential Application Of Oral Microbiota In the Preventi...mentioning
confidence: 99%